Interests of territorial self-governments in shaping local development on the example of tourism economy in Poland - selected aspects - Grabowska, Aleksandra; Krakowiak-Drzewiecka, Monika (Managerial Economics, 2014)
Communes in Poland are entities that act on market, have defined resources at their disposal, are independent, which is legally guaranteed, and are also responsible for their decisions. Moreover, they compete with each other for various forms of capital. Their effectiveness in management and rationality of undertaken actions are essential as they can reach a specific (desired) market position. In this paper, the assumption was made that relationships of entities interested in activities of commune can have a diversified nature (not necessarily favorable from the point of view of their goals and interests), and the power of their influence may significantly facilitate or impede management in a commune and thereby influence the effectiveness of its activity. In the present conditions of commune functioning, the ability to recognize the interests of particular entities related by market relationships with the commune may guarantee and, in the case of a lack of this ability, may limit the accomplishment of interests of a commune as a collective. The reflec- tions presented in this paper include broadly understood interests of local self-governments. This area is multi-dimensional and poorly recognized, which inspires us to make an attempt to create the system of notions. This attempt has been undertaken in further part of the paper. This constitutes an introduction to direct studies on the problems of interests of local self- government on the example of tourism economics